2003
DOI: 10.1074/jbc.m212021200
|View full text |Cite
|
Sign up to set email alerts
|

Caspase Proteolysis of Desmin Produces a Dominant-negative Inhibitor of Intermediate Filaments and Promotes Apoptosis

Abstract: 263 has important functional consequences, including the production of an amino-terminal cleavage product, N-desmin, which is unable to assemble into intermediate filaments, instead forming large intracellular aggregates. Moreover, N-desmin functions as a dominant-negative inhibitor of filament assembly, both for desmin and the structurally related intermediate filament protein vimentin. We also show that stable expression of a caspase cleavage-resistant desmin D263E mutant partially protects cells from tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
0
19

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 47 publications
6
72
0
19
Order By: Relevance
“…HSP20s and HSP70s inhibit apoptosis by sequestering pro-apoptotic factors such as Bax (Beere & Green, 2001;Concannon, Gorman, & Samalli, 2003). Apoptosis have been identified as a tenderization enhancer just after slaughtering by Ouali et al (2006), notably by protein proteolysis done by caspases, enzymes able to degrade structural proteins (Chen, Chang, Trivedi, Capetanaki, & Cryns, 2003;Nakanishi, Maruyama, Shibata, & Morishima, 2001). So, this is in contradiction with the positive role of HSP20s with tenderness.…”
Section: Discrimination Of St Tenderness Classesmentioning
confidence: 99%
“…HSP20s and HSP70s inhibit apoptosis by sequestering pro-apoptotic factors such as Bax (Beere & Green, 2001;Concannon, Gorman, & Samalli, 2003). Apoptosis have been identified as a tenderization enhancer just after slaughtering by Ouali et al (2006), notably by protein proteolysis done by caspases, enzymes able to degrade structural proteins (Chen, Chang, Trivedi, Capetanaki, & Cryns, 2003;Nakanishi, Maruyama, Shibata, & Morishima, 2001). So, this is in contradiction with the positive role of HSP20s with tenderness.…”
Section: Discrimination Of St Tenderness Classesmentioning
confidence: 99%
“…For example, it was reported that caspase-mediated cleavage of desmin is associated with apoptosis in muscle. 25 In addition, Limb Girdle muscular dystrophy type IIA is caused by mutation in protease calpain-3, a known activator of caspases, and apoptotic nuclei are observed in patients with this disorder. 26 Recently, several independent studies showed apoptotic myonuclei and caspase activation in myofibrillar myopathy.…”
Section: Homma Et Almentioning
confidence: 99%
“…Caspase 6 phosphorylates specific residues in desmin, induced by change in serum concentration that controls differentiation (50). Desmin has been described as a major substrate for proteolysis by a muscle-specific calpain (51).…”
Section: Molecular Interactionsmentioning
confidence: 99%